Навчальні програми та предмети, які викладалися в Чернігівській класичній чоловічій гімназії у XIX столітті - Рига, Д. (Сiверянський лiтопис, 2019)
У статті мова йде про навчальні програми та предмети, які викладалися в Чернігівській класичній чоловічій гімназії в XIX столітті. Значна увага приділена виховному процесу. Among the educational institutions of the XIX – the beginning of the XX century, the school
was occupied by a school in Chernihiv – a classical male gymnasium. Of course, the history of
the creation and operation of the Chernihiv Classical Gymnasium, has its own peculiarities.
From the very beginning of the activity, the gymnasium was free and vice versa.
Accordingly, teachers were divided into junior and senior, teachers and students followed the
director. Moral and physical punishment methods were prohibited.
Students studied subjects such as: history, mathematics, geography, statistics, sophisticated
sciences, political economy, philosophy, natural history, technology, commercial science, French,
Latin, German, painting.
In 1819, a single curriculum was introduced for all gymnasiums, which effectively
overthrew the previous reform of 1804. Corporal punishment was restored, religion has been
given a significant role. Increased training time. Training has been ongoing since then for 7
years.
On December 8, 1828, a new Statute was drafted, according to which the gymnasia had
to pursue the main goal – preparation for admission to universities in their studies.
Were introduced «corporal punishment» – cutting. Increased tuition fees, and a 2,5 times
increased salary statement. In 1852, the curricula of gymnasia change: the amount of teaching
of mathematics decreases, the tuition fee increases.
The statute of 1864 envisaged the formation of three types of gymnasiums: – classical
– with two ancient languages. – classical – with one Latin language – real – without old
languages. According to the draft, public schools were allocated as a separate school, which
was not at all connected with the gymnasium.
The school year in secondary schools began on August 16 and lasted until June 1, ie 240
days. Textbooks were only allowed for use, only approved by the Scientific Committee of the
Ministry. Final examinations were conducted in oral and written form. After the final exam,
a maturity certificate was issued. At the end of the school year there was a report on the work
of the gymnasium.
After the revolutionary events of 1917, the gymnasium was canceled. It is quite clear that
the secondary education of the «old model» did not correspond to the new conditions of social
and political life. Throughout the XIX – early XX century, the classical male gymnasium in
Chernigov, was a solid educational institution of the middle level.